Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1111/bph.12246
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen sulfide donor, GYY4137, exhibits anti‐atherosclerotic activity in high fat fed apolipoprotein E−/− mice

Abstract: Background and Purpose Atherosclerosis is associated with reduced vascular hydrogen sulfide (H2S) biosynthesis. GYY4137 is a novel slow‐releasing H2S compound that may effectively mimic the time course of H2S release in vivo. However, it is not known whether GYY4137 affects atherosclerosis. Experimental Approach RAW 264.7 cells and human blood monocyte‐derived macrophages were incubated with oxidized low density lipoprotein (ox‐LDL) with/without GYY4137. ApoE−/− mice were fed a high‐fat diet for 4 weeks and ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
131
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(141 citation statements)
references
References 47 publications
7
131
0
3
Order By: Relevance
“…Experimental evidence for an antiatherosclerotic effect of H 2 S has been obtained in numerous studies in hyperlipidemic animal and cell models (15,(24)(25)(26), but the antiatherosclerotic effect in the context of diabetes has not been previously investigated. Recent data published by our group demonstrated that treatment with H 2 S decreased aortic atherosclerotic plaque formation and partially restored aortic endothelium-dependent relaxation in ApoE 2/2 mice fed an HFD (15). Exogenous H 2 S improved endotheliumdependent relaxation in isolated vascular rings incubated with HG and attenuated hyperglycemia-induced DNA injury and improved cellular viability in bEnd.3 microvascular endothelial cells (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental evidence for an antiatherosclerotic effect of H 2 S has been obtained in numerous studies in hyperlipidemic animal and cell models (15,(24)(25)(26), but the antiatherosclerotic effect in the context of diabetes has not been previously investigated. Recent data published by our group demonstrated that treatment with H 2 S decreased aortic atherosclerotic plaque formation and partially restored aortic endothelium-dependent relaxation in ApoE 2/2 mice fed an HFD (15). Exogenous H 2 S improved endotheliumdependent relaxation in isolated vascular rings incubated with HG and attenuated hyperglycemia-induced DNA injury and improved cellular viability in bEnd.3 microvascular endothelial cells (8).…”
Section: Discussionmentioning
confidence: 99%
“…or vehicle and kept on a high-fat diet (HFD) for 4 weeks. The dose of GYY4137 used was based on previous publications (15). Nondiabetic LDLr 2/2 or LDLr 2/2 Nrf2 2/2 mice were kept on a standard chow diet for 4 weeks as control.…”
Section: Ldlrmentioning
confidence: 99%
“…In contrast to Na 2 S and NaSH, GYY4137 (morpholin-121 4-ium 4-methoxyphenyl-morpholino-phosphinodithioate) is a donor compound which 122 releases H 2 S at a slow steady rate at physiological pH and temperature (Li et al,123 2008). Several studies have suggested that GYY4137 effectively delivers H 2 S in 124 various physiological systems (Li et al, 2009, Lisjak et al, 2010, Lee et al, 2011 Robinson and Wray, 2012, Liu et al, 2013, Grambow et al, 2014 2015b). Recent work by Meng et al (2015a) showed that GYY4137 given prior to 127 7 …”
mentioning
confidence: 99%
“…NO and H 2 S share several athero-protective actions, including blood vessel relaxation and regulation of vascular tone, EC regeneration, inhibition of leukocyte adhesion, inhibition of platelet clumping to make the blood thinner, and prevention of proliferation and migration of VSMCs [150][151][152][153]. The role of NO in atherosclerosis development has been studied in apolipoprotein E knockout (apoE-KO) mice, where L-NAME treatment significantly decreased NO-mediated vascular response and increased atherosclerosis development [154].…”
Section: The Roles Of H 2 S and No In Atherosclerosismentioning
confidence: 99%
“…H 2 S (50 µM) attenuated H 2 O 2 and oxidized LDL (oxLDL)-mediated endothelial cytotoxicity in HUVECs [161]. GYY4137 (a slow H 2 S releasing molecule) decreased the atherosclerotic plaque formation and partially restored the endothelium-dependent relaxation of apoE-KO mouse aorta [162]. The direct evidence for the role of endogenous H 2 S in atherosclerosis development was reported in 2013, demonstrating that CSE-KO mice fed with atherogenic paigen-type diet, but not WT mice, developed early fatty streak lesions in the aortic root, increased aortic intimal proliferation and aortic adhesion molecule expression, and enhanced oxidative stress [28].…”
Section: The Roles Of H 2 S and No In Atherosclerosismentioning
confidence: 99%